Abnormal returns before acquisition announcements : evidence from Europe - Borges, Maria Rosa (2022)
Acquisition announcements influence the stock price of target firms, providing an opportunity for insiders to obtain significant abnormal returns. We study the presence of positive abnormal returns before the announcement date, in target firms, quoted in Euronext markets (Belgium, France, The Netherlands and Portugal) from 2001 to 2007. We investigate whether the pre-announcement run-up of prices can be explained by rumours in the media and the percentage of capital previously owned by the bidding firm, among other factors. We examine cumulative abnormal returns in an event window of 60 days prior the acquisition announcement, with the event date adjusted for the previous disclosure of news about the acquisition, in the media. We compute a run-up index, and find that there are abnormal positive returns before the announcement date, confirming previous studies. We find that a significant part of the run-up is explained by: (i) market anticipation triggered by legitimate sources of information, namely, rumours in the media about the possibility of an acquisition bid and (ii) the percentage of capital previously owned in the target firm, by the bidding firm..